How do males of Hypsiboas goianus (Hylidae: Anura) respond to conspecific acoustic stimuli? - Alessandro R. Morais; Mariana N. Siqueira; Rogério P. Bastos (Zoologia (Curitiba), 2015)
ABSTRACT Acoustic communication plays an important role in the social behavior of anurans. Acoustic signals, which can be used in different contexts such as mate attraction and territory defense, may mediate social interactions among individuals. Herein, we used playback experiments to test whether males of Hypsiboas goianus (Lutz, 1968) change their vocal behavior in response to conspecific advertisement calls. Specifically, we used different field playback experiments in which we modified the time interval between advertisement calls to simulate males with distinct states of motivation (Sequence A and B). We did not observe differences in the acoustic response of males of H. goianus between the two types of field playback experiments. On the other hand, we observed that H. goianus males reduce the dominant frequency of the advertisement call and increase the rate of aggressive calls in response to a conspecific competitor. Our results suggest that the acoustic plasticity observed in males of H. goianus represents an aggressive response that allows repelling conspecific individuals.